Winter care and feeding of young animals - Rahal, Anshu; Shivay, Yanshi; Shivay, Yashbir Singh (Indian Farming, 2021)
In India, winter creates havoc for both human and animals. The season mostly lasts for about four months. Human can adjust according to the changing environmental conditions but animals’ feed and shelter need to look after in an intensive system of farming. Due care of young animals is essential because of the breeding season and susceptible towards diseases during this period. About 32-35% mortality is noted between birth and 3 months of age in calves. Producers need to plan for shelter beforehand. Loss of young flock causes future monetary loss in a profitable herd. Regular deworming for both ecto and endoparasites are essential. Footrot and pneumonia are the major problems in winter with wet and cold temperature. In winter feeding depends on both feed availability and body condition scores of animals. Attention in winters for dairy calf and heifer management is of prime importance for maintaining growth rates, minimizing health problems, and optimizing the current and future profitability of the dairy farm.